Predicting marital adjustment based on borderline personality traits with the mediating role of defense styles - Mohammad Barzgar; Masoud Bagheri; Farzaneh Khosropoor (Fiyz̤, 2022)
Background: Personality disorders and defense styles are influential factors in marital adjustment. This study aimed to predict marital adjustment through borderline personality traits with the mediating role of defense styles. Materials and Methods: The research design was path analysis. The statistical population was married people aged 30 to 40 years who referred to family counseling centers and family courts of Rafsanjan in the spring and summer of 1398. 200 individuals were selected from the statistical population by available sampling method. Then they were given the Leichsenring Personality Traits Questionnaire (1999), the Spanier Marital Adjustment Questionnaire (1979), and the Andrews, Singh, and Bond (1993) Defense Styles Questionnaire. The obtained data were analyzed by path analyzing method, ANOVA, correlation coefficient and regression. Results: The results showed that borderline personality traits have a direct, negative and significant relationship with marital adjustment (β=-0.384, P<0.01) and a direct, positive and significant relationship with defense styles (β=0.242, P<0.01). Also, defense styles had a direct, negative and significant relationship with marital adjustment (β=-0.389, P<0.01). The results of Sobel test showed that defense styles are mediators between borderline personality traits and marital adjustment (Z-Value =-1.980, P<0.05). Conclusion: Based on the results of this study, it is necessary to pay attention to the role of defense styles in marital mutual understanding and adaptation of couples along with their personality traits.